Credit access, demand, and repayment among smallholder farmers in Nigeria: A follow-up analysis - Ambler, Kate; Balana, Bedru; Bloem, Jeffrey R.; Maruyama, Eduardo; Olanrewaju, Opeyemi (International Food Policy Research Institute, 2025)
Access to credit can be important for improving the performance of smallholders, as it enables farmers to purchase inputs while sustaining their livelihoods. In rural Nigeria, however, access to credit—particularly from formal financial institutions—is limited. As a result, farmers often have little to no choice but to depend on alternative credit sources, including informal lending. Small holder agricultural households often turn to friends and family, or local money lenders and other informal and semi-formal sources to meet their credit needs (EFInA, 2020).